2008
DOI: 10.1124/jpet.108.147082
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsins B and L Differentially Regulate Amyloid Precursor Protein Processing

Abstract: Previous studies have shown that cathepsins control amyloid beta (A␤) levels in chromaffin cells via a regulated secretory pathway. In the present study, this concept was extended to investigations in primary hippocampal neurons to test whether A␤ release was coregulated by cathepsins and electrical activity, proposed components of a regulated secretory pathway. Inhibition of cathepsin B (catB) activity with CA074Me or attenuation of catB expression through small interfering RNA produced decreases in A␤ releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 41 publications
(48 reference statements)
1
32
3
Order By: Relevance
“…Genetic inactivation of cathepsin B was also found to increase the abundance of A 1-42 and worsen the pathology. In striking contrast however, while the above studies strongly implicate cathepsin B activity in A clearance, others report that inhibition of cathepsin B reduces A production and release in chromaffin cells, primary hippocampal neurons, and hAPP mice expressing the wild-type -secretase site [89][90][91][92]. The mouse model exhibited a reduction in the characteristic memory deficit in association with the inhibitor's effect on A 1-42 , CTFs, and amyloid load.…”
Section: Lysosomal Modulationmentioning
confidence: 75%
See 1 more Smart Citation
“…Genetic inactivation of cathepsin B was also found to increase the abundance of A 1-42 and worsen the pathology. In striking contrast however, while the above studies strongly implicate cathepsin B activity in A clearance, others report that inhibition of cathepsin B reduces A production and release in chromaffin cells, primary hippocampal neurons, and hAPP mice expressing the wild-type -secretase site [89][90][91][92]. The mouse model exhibited a reduction in the characteristic memory deficit in association with the inhibitor's effect on A 1-42 , CTFs, and amyloid load.…”
Section: Lysosomal Modulationmentioning
confidence: 75%
“…With such evidence that cathepsin B contributes to the formation of amyloidogenic peptides, perhaps PADK, being both a cathepsin inhibitor and a positive modulator, can express multiple protective actions including blocking cathepsin B's production of toxic peptides through its inhibitory effect, and up-regulating cathepsin L levels to suppress the peptides. The latter stems from the report in which cathepsin L was found to reduce A levels [92], and it is of further interest that combined deficiency in cathepsins B and L leads to pathogenic accumulations, axonopathy, and subsequent neuronal loss [93]. It is important to note that PADK reduces CTFs and other accumulation events that are pre-existing in the slice model and whose production has been ceased by removal of chloroquine, thus suggesting that the lysosomal modulator primarily improves clearance rather than blocking cathepsin B's or other cathepsins' ability to generate amyloidogenic species.…”
Section: Lysosomal Modulationmentioning
confidence: 94%
“…Furthermore, gene silencing of cathepsin B by siRNA in normal WT hippocampal brain neurons (in primary culture) reduces the amount of Aβ in the regulated secretory pathway (Klein et al, 2009). These studies also showed that the CA074Me inhibitor reduces Aβ in the regulated secretory pathway of rat hippocampal neurons, indicating a role for cathepsin B in Aβ production.…”
Section: Validation Of the Cathepsin B Target By In Vivo Gene Knockoumentioning
confidence: 99%
“…Notably, inhibitors of cathepsin B reduced production of Aβ in the isolated regulated secretory vesicles (Hook et al, 2005). These inhibitors of cathepsin B also reduced production of Aβ in the regulated secretory pathway of hippocampal neurons (rat) (Klein et al, 2009). But these inhibitors had no effect on Aβ in the constitutive secretory pathway.…”
Section: Neurobiology Of Cathepsin B For Aβ Production In the Regulatmentioning
confidence: 99%
See 1 more Smart Citation